PEMAHAMAN MASYARAKAT TERHADAP MUSTAHIQ PENERIMAAN ZAKAT FITRAH KEPADA IMAM MASJID DAN DUKUN BERANAK - Nur Fajri Septiana; Patimah; Nila Sastrawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Abstract The main problem in this study is how the public's understanding of the mustahiq of receiving zakat fitrah to mosque priests and traditional birth attendants in Bontoa, Bontoa Village, Minasatene District, Pangkep Regency. Furthermore, this sub-problem is divided into three parts, namely. This study uses a qualitative field research method (field research) / field research that is descriptive in nature, with the research approach being an empirical juridical approach, Pangkep Regency still applies the tradition handed down from their ancestors, namely giving zakat fitrah to mosque imams and traditional birth attendants as well as to the poor. They do this because the community's understanding of mustahiq is still very lacking, besides that it is also a form of gratitude for the Bontoa people for the help given to them. According to the view of Islamic law, the acceptance of zakat fitrah to the Imam of the mosque is not yet valid because it is not classified in the context of fisabilillah. And the acceptance of zakat firah against traditional birth attendants is not valid, because it is not included in the mustahiq category. Keywords: Mustahiq, Zakat Fitrah, Taditional birth attendants.